An Intelligent Logistics Tracking System Based on Wireless Sensor Network - Jijun, Xing (International Journal of Online and Biomedical Engineering (iJOE), 2018)
In view of the shortcomings in information collection and tracking management in existing logistics, the key technologies of wireless sensor network and the basic concepts and methods of Information Technology Infrastructure Library(ITIL) is studied. The basic structure and main functions of the logistics tracking system based on wireless sensor network is put forward. It can effectively solve the detection, location, recognition and automatic processing of fault events and other issues of goods in the process of logistics tracking management. In addition, combined with the GIS software, the logistics tracking and monitoring system based on the wireless sensor network is realized by using Java language coding. The results show that this system can realize the tracking, visualization and automatic management of the information in the process of goods transportation. Therefore, the proposed method significantly improves the accuracy, rapidity and intuition of the logistics information management.